Analysis of the Economic Potential of Bangka Belitung Islamic Boarding Schools - Rahmat Ilyas; Rudi Hartono (Journal of Islamic Economic and Business Research, 2022)
Pondok Pesantren, the oldest traditional Islamic education institution, grows independently and develops among Muslims in Indonesia. The existence of pesantren has an important role as a pioneer in the spread of Islamic teachings in Indonesia. Islamic boarding schools have three main functions that are always carried out: First, as a center for the regeneration of religious thinkers. Second, as an institution that produces human resource cadres. Third, as an institution that has the power to empower the community. This study aims to analyze the economic potential of Islamic boarding schools, especially in Bangka Belitung. This research uses quantitative methods. The total population in this study was 34 Islamic boarding schools. The data used in this study were primary data. The data were collected through a questionnaire and then went through validity, reliability, and classical assumption tests. The results of this study indicate that the business potential of Islamic boarding schools in Bangka Belitung is very good. This can be seen from the research results showing that 91.18% have business potential, while those who do not have potential are 2.94%, and those with no sure business potential are 5.88%. Human resources (HR) potential in Islamic boarding schools are very good. This can be seen from the educational background, which reaches 74% for undergraduate, 3% for diploma III, and 23% are still at the elementary and high school level.